1999
DOI: 10.1175/1520-0442(1999)012<1458:rtinoe>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Regional Trends inNimbus-7OLR: Effects of a Spectrally Nonuniform Albedo*

Abstract: Data from the Earth Radiation Budget wide-field-of-view sensors on board the Nimbus-7 satellite during the period 1979-87 indicate a statistically significant downward trend in daytime outgoing longwave radiation (OLR) of up to 14 W m Ϫ2 decade Ϫ1 over the Sahara desert region of Africa. Reflected solar radiation shows a positive trend of the same magnitude. No significant trends in temperature or cloudiness over the region can be demonstrated. Atmospheric desert dust aerosols increase over the same period, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The debate surrounding trend estimation from long-term satellite-based records is not new, but it is of critical scientific importance to determine whether there is a small secular trend in a long-term albedo data set. This task is greatly complicated by the nearly inevitable drift in instrument calibration after launch [e.g., Hurrell and Trenberth, 1998] combined with the deleterious effects of near-Earth environment on instrument performance [e.g., Tashima and Hartmann, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…The debate surrounding trend estimation from long-term satellite-based records is not new, but it is of critical scientific importance to determine whether there is a small secular trend in a long-term albedo data set. This task is greatly complicated by the nearly inevitable drift in instrument calibration after launch [e.g., Hurrell and Trenberth, 1998] combined with the deleterious effects of near-Earth environment on instrument performance [e.g., Tashima and Hartmann, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, small long-term trends were noticed, but were not studied further as Tashima & Hartmann (1999) have reported that such trends in ORL (for example, observed by the Nimbus-7 satellite during [1979][1980][1981][1982][1983][1984][1985][1986][1987] were mostly instrumental in nature.…”
Section: Spectramentioning
confidence: 99%